Efektivitas Ekstrak Etanol Daun Sisik Naga pada Penyembuhan Luka Bakar Tikus Jantan - Putra, Rama Feriska; Desnita, Eka; Putri, Amanda Aprilia (CV. ITTC INDONESIA, 2026)
Burns are tissue injuries caused by hot liquids, chemicals, fire, or electric currents, and require proper treatment. Dragon scale leaves (Pyrrosia piloselloides (L.) M. G Price) contain bioactive compounds such as alkaloids, flavonoids, saponins, tannins, polyphenols, and steroids that may accelerate wound healing. This study aimed to evaluate the effect of dragon scale leaf ethanol extract and determine the effective concentration for burn healing in male rats. A post-test control group experimental design was used with 25 male rats divided into five groups: negative control (base gel), positive control (Bioplacenton®), and three extract groups at concentrations of 15%, 20%, and 25%. Burn wound diameter was measured on days 0, 3, 7, and 14. Significant differences between groups were observed on days 7 and 14 (p<0.05). On day 14, the 25% extract group showed the best healing among extract groups (26.95%), followed by 20% (19.37%) and 15% (15.01%). The positive control showed the highest healing rate (40.01%), while the negative control showed the lowest (14.01%). These findings indicate that dragon scale leaf ethanol extract, especially at 25%, accelerates burn wound healing.